EFFECT OF VULCANIZATION SYSTEMS AND CROSSLINK DENSITY ON TENSILE PROPERTIES AND NETWORK STRUCTURES OF NATURAL RUBBER (Jurnal Teknologi (Sciences & Engineering), 2022)
The mechanical properties of natural rubber (NR) vulcanizate depend strongly on several factors, i.e., vulcanization systems and crosslink density. These two parameters are originally from the formulation design of the vulcanizate. To focus more on such details, influences of three different vulcanization systems (sulfur, peroxide, and phenolic resin) with variations in their crosslink densities were studied by focusing on the change of curing properties, crosslink densities, mechanical properties and network structures of the NR vulcanizates. The crosslink density of various vulcanization systems increased with increasing curing promotors, as revealed by temperature scanning stress relaxation measurement. The tensile modulus at 100% strain increased with increasing crosslink density in all systems but the tensile strength varied with the vulcanization systems and degree of crosslink density. At the same crosslink level, the greatest tensile strength was obtained when the sulfur was used as a crosslinker, which was 100% greater than those obtained from peroxide and 200% over phenolic systems. In comparison to the phenolic resin system, sulfur and peroxide crosslink systems had a more uniform distribution of the crosslink network structure. The size of the network structure was found to be independent of the tensile strength. The peroxide system had the most uniform distribution of the crosslink network structure.